Powder mixture for teflon-free non-stick coatings

By using a powder mixture of PAEK and PPS polymers, an efficient non-stick coating is formed, which solves the health and environmental problems of fluoropolymers and PFAS in the prior art, and achieves an efficient and environmentally friendly non-stick effect.

CN119855877APending Publication Date: 2025-04-18ACS COATING SYST GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380061341.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-23
Filing Date
2023-08-22
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The use of fluoropolymers and PFAS in existing non-stick coatings has health risks and environmental pollution problems, while the ceramic coating is not durable.

Method used

A powder mixture consisting of polyaroketone (PAEK) and polyphenylene thiol (PPS) polymers is used to form a non-stick coating by high temperature hydrolysis and polycondensation, avoiding the use of fluorine or fluorine-containing compounds.

Benefits of technology

A high-efficiency non-stick effect is achieved without adding oil and no need for fluorine-containing surfactants, and significantly reduce material use and energy input, while improving the mechanical resistance and wear resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119855877A_ABST
    Figure CN119855877A_ABST
Patent Text Reader

Abstract

The invention relates to a powder mixture, dry or as a dispersion in a liquid, comprising powder particles consisting of at least one polyaryletherketone (PAEK) polymer and optionally a polyphenylene sulfide (PPS) polymer, the powder mixture being able to be produced without the addition of fluorine or fluorine-containing compounds. Preferably, the powder mixture comprises a total fluoride of up to 1000 ppb, preferably up to 100 ppb, especially preferably up to 25 ppb, as measured by combustion ion chromatography (TOF-CIC). The invention further relates to a method for coating objects, in particular cooking and baking fittings, with a powder mixture, to the use of a powder mixture for achieving technical effects selected from the group consisting of non-stick effects and anti-corrosion protection, and to objects coated by the method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a powder mixture for a Teflon-free non-stick coating, a method for coating objects, in particular cooking and baking accessories, with the powder mixture, the use of the powder mixture for achieving a non-stick and smooth effect on objects, in particular cooking and baking accessories, and an object, in particular cooking and baking accessories, coated by the method. Background Art

[0002] PTFE coatings are known from the prior art, which for high-quality cookware are usually applied as a three-layer coating, i.e. in three layers with usually at least two baking steps. In this case, the base layer, which usually consists of a binder resin dissolved in a solvent, for example PAI dissolved in NMP, is first wet-sprayed, dried and pre-crosslinked. Then, the transition layer and the cover layer are sprayed wet-on-wet, wherein the cover layer mainly contains fluoropolymers, usually PTFE. The entire coating is then baked at 420° C. for about 10 minutes. These coatings can be modified with pigments and various fillers. Disadvantages are the use of fluoropolymers and the fact that the baking temperature is significantly higher than the decomposition temperature of PTFE, which can produce substances that are harmful to health (PFAS). In addition, it has the disadvantage of releasing toxic substances (PFAS) when used at high temperatures.

[0003] Furthermore, so-called ceramic sol-gel coatings are known which contain silicones in order to achieve a non-stick effect, but are usually very brittle and not durable.

[0004] According to EU regulations, the limit values ​​for PFAS in the EU are to be reduced significantly from 2024, so that PTFE coatings ("Teflon") as non-stick coatings must be replaced from today's perspective. Summary of the invention

[0005] The object of the present invention is a universally applicable coating for objects, in particular for cooking and baking utensils, which is free of fluoropolymers and free of fluorine additives.

[0006] The above objects are achieved by providing a powder mixture according to claim 1, a method according to claim 8, a use according to claim 10, an object, in particular a cooking and baking accessory, according to claim 12 or 13. Preferred embodiments are shown in the dependent claims. The term cooking and baking accessories according to the invention encompasses any form of object suitable for receiving food and subsequently cooking and baking it. Thus, in addition to pots, the above term also includes baking trays, baking molds, etc., as well as grilling trays, grilling containers, grilling grates, etc.

[0007] In a first aspect according to the invention, a powder mixture is provided dry or as a dispersion in a liquid, the powder mixture comprising powder particles of at least one polyaryletherketone (PAEK) polymer and optionally a polyphenylene sulfide (PPS) polymer.

[0008] The powder mixture according to the invention can be produced without adding fluorine or fluorine-containing compounds. This is the case in particular according to the invention if the powder mixture does not exceed a specific limit value for total fluoride when it is baked at 900° C. to 1000° C. in a moist, oxygen-rich atmosphere. Preferably, the powder mixture therefore contains a total fluoride of not more than 1000 ppb, preferably not more than 100 ppb, particularly preferably not more than 25 ppb, as measured by combustion ion chromatography (TOF-CIC).

[0009] In detail, in order to carry out the measuring method of combustion ion chromatography (TOF-CIC), according to the invention, a sample of the powder mixture is loaded into a ceramic baking boat and introduced into an oven, where a pyrolysis occurs at 900° C. to 1000° C. in a moist, O2-rich environment. The sample is oxidized under the conditions, the strong carbon-fluorine bonds are broken, and the vapor is conducted through an absorption solution with Ar. The HF generated during the baking of the organic fluorine decomposes in the absorption solution under the conditions of forming H+ and F- ions. A sample of the absorption solution, which also contains an internal standard for calibrating the analytical results, is then transferred to an ion chromatograph for analysis, where the fluoride is measured.

[0010] Surprisingly, the powder mixture according to the invention is particularly suitable for coating objects, in particular cooking and baking accessories. The non-stick effect of the coating produced with the aid of the powder mixture according to the invention (tested with the aid of a standard pancake according to DIN EN 60350-2) corresponds to the expectations for a non-stick effect for cooking utensils without the addition of oil and without any fluorine components. In particular, no fluorinated surfactants are required to promote distribution when using the powder mixture according to the invention for producing coatings.

[0011] Another advantage is that only one, and to be more precise, relatively thin, layer is required in order to meet all requirements for non-stick coatings for food contact. According to the prior art, wear-resistant three-layer polytetrafluoroethylene (PTFE) coatings with a layer thickness of approximately 50 μm-60 μm are currently common. With the current coatings of approximately 20 μm-30 μm, in addition to completely avoiding perfluorinated or polyfluorinated alkyl compounds, the use of materials, volatile organic compounds (VOC) and energy input can be significantly reduced.

[0012] Preferably, the powder mixture comprises at least two polymers, wherein the powder particles comprising the first polymer have a mass-related particle size distribution D50 measured by still image analysis according to ISO 13322-1:2014 of up to 70 μm, preferably up to 60 μm, more preferably up to 50 μm, even more preferably up to 40 μm, in particular up to 30 μm, and the powder particles comprising the second polymer have a mass-related particle size distribution D50 measured by still image analysis according to ISO 13322-1:2014 of up to 30 μm, preferably 25 μm, more preferably up to 20 μm, even more preferably up to 15 μm, particularly preferably 10 μm. As a result, the mechanical resistance can be increased. This can be achieved by adding PEK and / or PEKK. Smaller mass concentrations of at least 2% by weight, preferably at least 5% by weight, particularly preferably at least 10% by weight of the second polymer have shown a wear-reducing effect.

[0013] By contrast, by adding PPS in an amount of up to 80%, 90% or 95% by weight, a further reduction in the baking temperature during the production of the coating and a further improvement in the non-stick effect of the produced coating can be measured.

[0014] Preferably, the powder mixture is present as a dispersion and preferably the liquid comprises water in the dispersion.

[0015] Preferably, the powder mixture comprises at least two PAEK polymers, or at least one PAEK polymer and a PPS polymer, wherein the PAEK polymer is preferably selected from the group consisting of polyetheretherketone (PEEK), polyetherketone (PEK), polyetherketoneketone (PEKK) and polyetherketoneketoneetherketone (PEKKEK). Preferably, the polymers have different melting temperatures and / or preferably have different melt viscosities.

[0016] Preferably, the average melt viscosity of the at least one polymer, measured at 400° C. in accordance with ISO 11443, is at most 150 Pa.s, preferably at most 120 Pa.s, more preferably at most 100 Pa.s or particularly preferably at most 90 Pa.s. As a result, the distribution on the surface to be coated becomes significantly smoother when heated to polycondensation. The non-stick effect of the surface of the coating is thereby improved. This applies even in the case where the particles are large relative to the layer thickness (e.g. a particle size D50 of 25 μm for a layer thickness of 25 μm).

[0017] Preferably, the powder mixture further comprises an element from the following group: polyamideimide (PAI), polyimide (PI), graphite, MoS2 and mixtures thereof. This makes it possible to further improve the wear resistance.

[0018] In a second aspect according to the present invention, a method for coating an object, in particular a cooking and baking accessory, is provided. The method comprises the following steps:

[0019] - applying the powder mixture according to the invention to objects, in particular cooking and baking accessories, wherein the application is preferably carried out electrostatically in a vortex sintering process or as a dispersion in a liquid, in particular water;

[0020] - Complete removal of liquid in the case of dispersions;

[0021] - heating the powder mixture to form a polycondensate; and

[0022] - The powder mixture is baked at a temperature above the melting temperature of the polymer.

[0023] Preferably, the baking temperature (substrate temperature) is higher than the liquidus temperature of the polycondensate by at most 60° C., preferably at most 50° C., more preferably at most 40° C., still more preferably at most 30° C., and particularly more preferably at most 20° C. Experiments have shown that the non-stick effect changes as the baking temperature decreases or becomes worse in the case of too high a baking temperature.

[0024] Preferably, the method is performed without using a fluorosurfactant, especially in the step of heating the powder mixture to form the polycondensate.

[0025] In a third aspect according to the invention, a powder mixture for coating objects, in particular cooking and baking accessories, is used to achieve a technical effect selected from the following group: a non-stick effect checked with the aid of a standard pancake (DIN EN 60350-2); an electrical insulation of at least 1 V, preferably at least 2 V, further preferably at least 3 V, even further preferably at least 4 V, and particularly preferably at least 5 V measured in a 5% salt solution on the coated inner surface of the object, in particular cooking and baking accessories, to ensure sufficient corrosion protection for the metal substrate of the object, in particular cooking and baking accessories; and combinations thereof.

[0026] In a fourth aspect according to the invention, an object, in particular a cooking and baking accessory, is provided, which has a coating produced according to the method according to the second aspect according to the invention. Preferably, the average thickness of the coating is at most 50 μm, preferably at most 40 μm, further preferably at most 25 μm, particularly preferably at most 25 μm. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The invention is explained in more detail below with reference to exemplary embodiments and the associated drawings.

[0028] The drawings serve only to provide a better understanding of the invention and are only schematic and not designed to scale. The invention is not intended to be limited to the exemplary embodiments. Identical or identically acting components are provided with the same reference numerals.

[0029] Figure 1 shows a schematic cross section of a cooking and baking accessory with an applied dispersion layer,

[0030] Figure 2 A cooking and baking accessory having a coating according to the invention is shown,

[0031] FIG. 3 shows the method sequence during coating according to different method stages,

[0032] Figure 4 A flow chart is shown for coating by means of the dispersion method. DETAILED DESCRIPTION

[0033] The object to be coated or the area of ​​the cooking and baking accessories to be coated is the substrate SU to be coated. The surface to be coated can first be subjected to a chemical and / or mechanical activation treatment. For this purpose, mechanical roughening by means of a sandblaster, for example, or etching by means of an acid, alkali or plasma treatment or a laser treatment can be used. The correspondingly pretreated surface has additional chemical / physical bonding sites, is cleaner and free of grease, and has a larger surface in the case of roughening, which leads to better adhesion of the coating to be applied.

[0034] A layer DS of a dispersion is then applied to the surface, which contains all components of the coating in a dispersed manner in a solvent or solvent mixture in a finely divided and as uniform a particle size distribution as possible. The following application method is selected, which is suitable for producing the desired layer thickness. The average particle size (D50) of the solids contained in the dispersion corresponds at most to the desired layer thickness for the coating, but is preferably selected to be smaller. Figure 1 Such a coated substrate SU is shown with an applied dispersion layer DS.

[0035] After carrying out a temperature program in which the substrate or cooking and baking accessory provided with the dispersion layer DS is heated to a temperature above the melting point of the thermoplastic or thermoplastics contained in the dispersion, a uniform coating BS is obtained which is non-porous and therefore dense and has good mechanical bonding and good adhesion to the substrate SU. Figure 2 The finished cooking and baking accessories are shown.

[0036] It is possible here to carry out the coating only on sub-areas of the surface. The remaining, uncoated areas can be masked here, or a method of applying the dispersion can be selected which can differentiate between different surface areas, for example painting or printing. Masking can also be carried out with the aid of a shadow mask during the spraying of the dispersion. The shadow mask can also be designed in the form of a film which is applied to the surface of the substrate SU and leaves the areas of the surface to be coated free. After the dispersion layer DS has been applied, the film can be removed and, for example, peeled off, wherein the areas of the dispersion layer DS applied thereto are also peeled off.

[0037] FIG. 3 shows a variant of the method, with which a higher layer thickness can be achieved despite the fact that the particle diameter of the solids contained in the dispersion is selected to be small. For this purpose, after the first dispersion layer DS1 has been applied, as shown in FIG. 3a, at least the solvent is removed, and alternatively or additionally the first dispersion layer is still correspondingly pre-compacted by temperature treatment. In a second step, the dispersion coating is repeated and the second dispersion layer DS2 is applied. If necessary, the layers can also be pre-compacted and the coating step repeated again. Finally, as shown in FIG. 3c, the structure of the dispersion layer consisting of a plurality of sub-layers is exposed in a final step to a temperature above the melting point of the thermoplastic, whereby a completely compacted, pore-free, closed coating BS is obtained on the substrate SU.

[0038] Compositions suitable for application by means of a dispersion method and also for reducing friction according to the invention contain, for example, the following mass proportions of solids:

[0039] 100% PEEK by weight

[0040] If necessary, color additives can be added. It is possible to apply one or more layers.

[0041] The solids are dispersed, if necessary with the aid of auxiliaries, in a solvent which can be water or which is advantageously miscible with water or miscible with water, such as ethanol and in particular isopropanol. The dispersion mixture then contains approximately 30% by weight of the above-mentioned solids.

[0042] exist Figure 4 The process flow is shown again more clearly in FIG. 1 by means of a flow chart. The process comprises, as step 1, the preparation and provision of a powder mixture. For this purpose, the components selected from the thermoplastic polymer, filler and dry lubricant are brought to a suitable particle size, preferably by grinding and / or subsequently sorted according to the particle size according to the desired particle size distribution which is as narrow as possible.

[0043] In parallel, a solvent is prepared in step 2, which is preferably harmless to the environment and health, preferably water-based and in particular consists of a mixture of ethanol and water, for example isopropanol and water. Advantageous solvent compositions contain, for example, 25 to 75 weight percent isopropanol in water. Particularly preferred are solvents containing about 25-50 weight percent isopropanol in water.

[0044] In step 3, a dispersion is prepared by adding a solvent to the prepared powder mixture, wherein the solids content is preferably maintained at 20 to 50 weight percent. To improve the dispersion stability, small portions of known dispersion auxiliaries can be added.

[0045] In step 4, the surface of the object is coated, for example, by spraying, dipping, painting, printing or centrifugal coating. The aim is to achieve a layer thickness of the dispersion layer that is as uniform as possible, and if necessary, areas of the coating surface that are not to be coated can be omitted.

[0046] In step 5 , the solvent is removed, preferably by evaporation, which can optionally be assisted by reduced pressure or elevated temperature, for example 80° C.

[0047] In the next step 6 , the cooking and baking accessory with the applied dried dispersion layer is converted into a homogeneous coating by heating and melting of the thermoplastic and the cooking and baking accessory is subsequently cooled again.

[0048] After said step 6, at point 7 the finished coating can be obtained.

[0049] According to a variant V1 of the method, it is possible to carry out steps 4 to 7 again directly after step 5 .

[0050] The second variant V2 follows step 6 , in which a new dispersion layer is applied after the melting of the first dispersion layer (step 4 ) and is correspondingly compacted (steps 5 to 7 ).

[0051] According to a third method variant V3, after the first coating has been produced according to step 6, a second sublayer of the coating, which is different from the first coating, is applied. For this purpose, a further dispersion is produced according to method steps 1 to 3 and the cooking and baking accessories are coated according to steps 4 to 6. In this case, the methods according to variants V1 and V2 can also be modified by repeating individual method steps or individual method sequences in order to achieve the desired layer thickness.

[0052] Particularly when fine-grained particles are used for the dispersion, particularly uniform coatings can be achieved, which, due to the small particle diameters, make multiple coatings advantageous or necessary.

[0053] Although the invention is explained only on the basis of some exemplary embodiments, the invention is not limited to said exemplary embodiments. Possible variants are obtained in particular by suitable selection of fillers and, if necessary, by mixing different fillers. The used quantitative relationship of the components of the coating is selected according to the desired load of the coating. Likewise, the layer thickness is not limited to the examples described. Advantageously, the coating is applied to a metal surface, wherein the coating can however also be carried out on other surfaces, for example on ceramics, glass or suitable plastics.

[0054] Examples

[0055] The pan coating is produced as follows: an aqueous dispersion with a solvent content of 25% and a solid content of 30% is produced. The solid consists of PEEK from Victrex, which has an average mass-related particle size D50 of 10 μm and a given average melt viscosity of 150 Pa.s (120-180 Pa.s) measured at 400° C. according to ISO 11443. The substrate in the form of an aluminum pan is cleaned and degreased and then sandblasted. The Rz after sandblasting is about 20 μm (measured by scanning or non-contact optical roughness measurement). The aqueous PEEK dispersion is sprayed on with the aid of a conventional spray gun, dried at a temperature of about 50° C. and subsequently baked at an oven temperature of 400° C. This results in an optically closed, non-porous surface with a roughness of about Rz 20 μm (measured by scanning or non-contact optical roughness measurement).

[0056] However, in subsequent migration tests carried out to demonstrate compliance with legal limit values, it was found that the prescribed limits could not be met because the coating was too thin to adequately cover the metal substrate. In subsequent experiments, the baking temperature was increased in order to improve the distribution due to the resulting lower melt viscosity. Surprisingly, it was found that the non-stick effect decreased with increasing baking temperature. Conversely, lowering the baking temperature improved the non-stick effect.

[0057] Surprisingly, further experiments have shown that the addition of a PEEK type with a lower melt viscosity of 90 Pa.s, even with a particle size D50 of 25 micrometers, i.e. the same layer thickness as that to be achieved, leads to a smoother, undisturbed distribution and an improved non-stick effect. In particular, the baking temperature can be reduced by 30°C, i.e. to an oven temperature of 370°C and a maximum substrate temperature of 360°C.

[0058] The non-stick effect was checked with the aid of a standard pancake (DIN EN 60350-2). The non-stick effect of the coating produced in this way corresponds to the expectations for a non-stick effect for cooking utensils, without the addition of oil and without any fluorine components. In particular, no fluorinated surfactants are required to promote the spreading with the coating according to the invention.

[0059] Another advantage is that only one, or rather a relatively thin layer, is required in order to meet all requirements for non-stick coatings for food contact. According to the prior art, wear-resistant PTFE coatings are currently three-layered with a layer thickness of approximately 50-60 micrometers. With the current coatings of approximately 20-30 micrometers, in addition to completely avoiding PFAS, the material, VOC and energy input can be significantly reduced.

[0060] In a further experiment, the mechanical resistance was to be increased. This could be achieved by adding PEK and / or PEKK. Smaller concentrations of 10.5 or 2% already showed a wear-reducing effect.

[0061] The wear resistance can be further improved by adding elements from the following group: polyamideimide (PAI), polyimide (PI), graphite, MoS2 and mixtures thereof.

[0062] On the contrary, by adding PPS in the order of magnitude of up to 80%, 90%, 95%, a further reduction in the baking temperature and a further improvement in the non-stick effect can be measured.

[0063] It was completely unexpected in the experiments that the melting temperature after baking is increased by mixing different polymer types. This ensures that the coating of the pan does not become liquid. In the pan, the surface temperature during use can reach over 300° C., with the melting temperature of the coating of the reference pan being 340° C., for example. Rather, it is not due to the concentration between the two temperatures of the two polymers involved, but rather to the concentration of the polymer with the higher or even higher melting point. In particular, it was measured that the coating according to the invention composed of PEEK and PEK does not become liquid up to 400° C. and above. But even a coating composed of PEEK and PPS, with a PPS concentration of 90%, does not become liquid up to 380° C., despite the melting points of the individual polymers being 285° C. and 340° C., respectively.

Claims

1. A powder mixture, dry or as a dispersion in a liquid, comprising powder particles of at least one polyaryletherketone (PAEK) polymer and optionally a polyphenylene sulfide (PPS) polymer, wherein the powder mixture can be produced without adding fluorine or fluorine-containing compounds.

2. The powder mixture according to claim 1, Therein, the powder mixture comprises a total fluoride content of not more than 1000 ppb, preferably not more than 100 ppb, particularly preferably not more than 25 ppb, measured by combustion ion chromatography (TOF-CIC).

3. The powder mixture according to claim 1 or 2, wherein the powder mixture comprises at least two polymers, and the powder particles comprising the first polymer have a mass-related particle size distribution D50, measured by still image analysis according to ISO 13322-1:2014, of at most 70 μm, preferably at most 60 μm, more preferably at most 50 μm, even more preferably at most 40 μm, in particular at most 30 μm, and the powder particles comprising the second polymer have a mass-related particle size distribution D50, measured by still image analysis according to ISO 13322-1:2014, of at most 30 μm, preferably 25 μm, more preferably at most 20 μm, even more preferably at most 15 μm, in particular preferably 10 μm.

4. A powder mixture according to any one of the preceding claims, wherein the powder mixture is present as a dispersion and the liquid comprises water.

5. A powder mixture according to any one of the preceding claims, The powder mixture comprises at least two PAEK polymers, or at least one PAEK polymer and a PPS polymer, wherein the PAEK polymer is preferably selected from the group consisting of polyetheretherketone (PEEK), polyetherketone (PEK), polyetherketoneketone (PEKK) and polyetherketoneketoneetherketone (PEKKEK).

6. The powder mixture according to claim 5, The polymers described have different melting temperatures.

7. The powder mixture according to claim 5 or 6, The PAEK polymers described therein have different melt viscosities measured in accordance with ISO 11443 at 400° C.

8. A powder mixture according to any one of the preceding claims, Therein, the at least one polymer has an average melt viscosity, measured at 400° C. to ISO 11443, of at most 150 Pa.s, preferably at most 120 Pa.s, more preferably at most 100 Pa.s or especially preferably at most 90 Pa.s.

9. A powder mixture according to any one of the preceding claims, The powder mixture further comprises an element from the following group: polyamideimide (PAI), polyimide (PI), graphite, MoS 2 and mixtures thereof.

10. A method for coating an object, in particular a cooking and baking accessory, comprising the steps of: - applying the powder mixture according to any one of claims 1 to 9 to an object, in particular a cooking and baking accessory, wherein the application is preferably carried out electrostatically in a vortex sintering method or as a dispersion in a liquid, in particular water; - Complete removal of liquid in the case of dispersions; - heating the powder mixture to form a polycondensate; and - The powder mixture is baked at a temperature above the melting temperature of the polymer.

11. The method according to claim 10, The baking temperature (substrate temperature) is at most 60°C, preferably at most 50°C, more preferably at most 40°C, still more preferably at most 30°C, and even more preferably at most 20°C higher than the liquidus temperature of the polycondensate.

12. The method according to claim 10 or 11, The method described herein, in particular in the step of heating the powder mixture to form a polycondensate, is performed without using a fluorosurfactant.

13. Use of a powder mixture according to any one of claims 1 to 9 for coating objects, in particular cooking and baking accessories, to achieve a technical effect selected from the following group: a non-stick effect checked with the aid of a standard pancake (DIN EN 60350-2); an electrical insulation of at least 1 V, preferably at least 2 V, further preferably at least 3 V, even more preferably at least 4 V, and particularly preferably at least 5 V measured in a 5% salt solution on the coated inner surface of the object, in particular the cooking and baking accessory, to ensure sufficient corrosion protection for the metal substrate of the object, in particular the cooking and baking accessory; and combinations thereof.

14. An object, in particular a cooking and baking accessory, having a coating produced according to the method according to any one of claims 10 to 12. 15 . The object, in particular a cooking and baking accessory, according to claim 14 , wherein the thickness of the coating is at most 50 μm, preferably at most 40 μm, further preferably at most 30 μm, particularly preferably at most 25 μm.